Predictive value of upper lip bite test and ratio of height to thyromental distance compared to other multivariate airway assessment tests for difficult laryngoscopy in apparently normal patients - Pratibha Jain Shah; Kamta Prasad Dubey; Jai Prakash Yadav (Wolters Kluwer Medknow Publications, 2013)
Background: Various anatomical measurements and non-invasive clinical tests, singly or in various combinations can be performed to predict difficult intubation. Recently introduced "Upper lip bite test" (ULBT) and "Ratio of height to Thyromental distance" (RHTMD) are claimed to have high predictability. We conducted a study to compare the Predictive Value of ULBT and RHTMD with Mouth opening (Inter-Incisor gap) (IIG), Modified Mallampatti Test (MMT), Head and neck movement (HNM) and Thyromental Distance (TMD) for Difficult Laryngoscopy. Materials and Methods: In this prospective, single blinded observational study, 480 adult patients of either sex, ASA grade I and II were assessed and graded for ULBT, RHTMD, TMD, MMT, IIG, and HNM according to standard methods and correlated with the Cormack and Lehane grade. Results: ULBT and RHTMD had highest sensitivity, specificity, positive predictive value, negative predictive value, likelihood ratio, i.e., 74.63%, 91.53%, 58.82%, 95.7%, 31.765 and 71.64%, 92.01%, 59.26%, 95.24%, 8.96 respectively, compared to TMD, MMT, IIG and HNM. Conclusions: ULBT is the best predictive test for difficult laryngoscopy in apparently normal patients but RHTMD can also be used as an acceptable alternative.